Localization of the cannabinoid CB1 receptor and the 2-AG synthesizing (DAGLα) and degrading (MAGL, FAAH) enzymes in cells expressing the Ca(2+)-binding proteins calbindin, calretinin, and parvalbumin in the adult rat hippocampus - Rivera-González, Patricia; Arrabal, Sergio; Cifuentes-Rueda, Manuel; Mateos-Grondona, Jesús; Pérez-Martín, Margarita; Rubio-Lamia, Leticia Olga; Vargas, Antonio; Serrano, Antonia; Pavón, Francisco Javier; Suárez-Pérez, Juan; Rodriguez de Fonseca, Fernando (Frontiers, 2014)
The retrograde suppression of the synaptic transmission by the endocannabinoid sn-2-arachidonoylglycerol (2-AG) is mediated by the cannabinoid CB1 receptors and requires the elevation of intracellular Ca(2+) and the activation of specific 2-AG synthesizing (i.e., DAGLα) enzymes. However, the anatomical organization of the neuronal substrates that express 2-AG/CB1 signaling system-related molecules associated with selective Ca(2+)-binding proteins (CaBPs) is still unknown. For this purpose, we used double-label immunofluorescence and confocal laser scanning microscopy for the characterization of the expression of the 2-AG/CB1 signaling system (CB1 receptor, DAGLα, MAGL, and FAAH) and the CaBPs calbindin D28k, calretinin, and parvalbumin in the rat hippocampus. CB1, DAGLα, and MAGL labeling was mainly localized in fibers and neuropil, which were differentially organized depending on the hippocampal CaBPs-expressing cells. CB(+) 1 fiber terminals localized in all hippocampal principal cell layers were tightly attached to calbindin(+) cells (granular and pyramidal neurons), and calretinin(+) and parvalbumin(+) interneurons. DAGLα neuropil labeling was selectively found surrounding calbindin(+) principal cells in the dentate gyrus and CA1, and in the calretinin(+) and parvalbumin(+) interneurons in the pyramidal cell layers of the CA1/3 fields. MAGL(+) terminals were only observed around CA1 calbindin(+) pyramidal cells, CA1/3 calretinin(+) interneurons and CA3 parvalbumin(+) interneurons localized in the pyramidal cell layers. Interestingly, calbindin(+) pyramidal cells expressed FAAH specifically in the CA1 field. The identification of anatomically related-neuronal substrates that expressed 2-AG/CB1 signaling system and selective CaBPs should be considered when analyzing the cannabinoid signaling associated with hippocampal functions.
Keywords: Inmunoquímica; Hipocampo (Cerebro); Microscopía confocal; Proteínas transportadoras del calcio; Modelos animales en investigación; 2-arachidonoylglycerol; Cannabinoid receptor; Calcium-binding protein; Confocal microscopy; Hippocampus; Immunohistochemistry; Rat